Comparing Articaine brands: A randomized non-inferiority controlled trial. Issue 6 (June 2021) - Arboleda-Toro, D.; Toro, L.; Osorio-Osorno, Y.A.; Castrillon-Pino, L.; Florez-Zapata, N.M.V.
Abstract: Introduction: The substitution of reference drugs for similar, new or existing drugs in the market is a dilemma present in daily dental procedures. In order to decide whether or not to adopt a new drug in relation to the reference, a clinical trial can provide the necessary evidence. Methods: A total of 179 healthy volunteers (18–25 years) requiring extraction of mandibular third molars completed the study. Subjects were randomized into 4 groups: right, left, Arteek-SP and Septanest. Allocations consisted of 4% Articaine hydrochloride with 1:10000 epinephrine. The primary aim of this randomized controlled trial was to determine whether the test drug Arteek-SP was noninferior by a margin of 10% in the proportion of patients with total absence of pain, compared to the reference drug Septanest in the extraction of mandibular third molars using inferior alveolar nerve blocks. Secondary outcomes included, hemodynamic parameters, volume (mL), pain scores assessed during one visit and reported postoperative discomfort assessed during 8 days. Noninferiority was declared if total absence of pain for both groups was equal to 0.9, with a significance level of 5% (P < 0.05) and power at 90% (β = 0.1) at 95% confidence level. Results: Arteek-SP was applied during the first surgery to 90 volunteers (50.28%) and Septanest was applied to 89 subjects (49.72%). Less than 10% difference was identified, in the proportion of patients with total absence of tooth pain P < 0.05 and in the gum P < 0.1, at 95% CI, when Arteek-SP was applied first in comparison with Septanest, establishing noninferiority. Conclusion: The clinical performance of the test drug Arteek-SP is noninferior to the reference drug Septanest. They can be considered interchangeable in terms of cost or convenience. Registration: ClinicalTrials.org, number NCT4166890. Abstract : Local anesthetics, amides, pain, oral surgery, nerve block, clinical studies.